Nickel-based complex crystal material and preparation method and application thereof
Through the combination of nickel-based cooperative crystal materials and 1,4-double (imidazole-1-base) benzene BIB and L-glutamic acid, the complexity and low sensitivity of copper ion detection methods in the existing technologies are solved. CU2+recognition with high selectivity and high sensitivity is suitable for portable detection applications.
Patent Information
- Application Number
- CN202411686692.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-25
AI Technical Summary
In the prior art, the copper ion (Cu2+) detection method is complex in operation, time-consuming, low sensitivity, low selectivity and high cost, making it difficult to develop portable, low-cost and high-sensitivity detection sensors.
The nickel-based clustering material is used as a ligand and auxiliary with the 1,4-two (imidazole-1-base) benzene BIB and L-glutamic acid, forming a CU2+recognition material with high selectivity and sensitivity.
A high -selective recognition of CU2+has been realized, the fluorescent ham reached 99.54%, and the material has good thermal stability, which is suitable for application in high temperature and complex environments.
Smart Images

Figure CN119161393B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of crystalline materials, and the technology relates to metal-organic coordination polymer materials, and in particular to a nickel-based complex crystal material and a preparation method and application thereof. Background Art
[0002] Copper is an essential trace element for the human body and a component of many enzymes and proteins. 2+ It can affect the activity of enzymes, activate the functions of kinases and transcription factors, and trigger the self-destruction mechanism of cancer cells under certain conditions. 2+ Intake helps prevent cancer. 2+ Cu is an important component of neurotransmitters and plays a key role in maintaining the balance of neurotransmitters and stabilizing emotions and behaviors. 2+ It can exist inside and outside red blood cells, helping iron transfer protein and catalyzing the synthesis of hemoglobin, which can significantly speed up blood circulation and improve physical health. 2+ It may cause neurological symptoms such as memory loss, confusion, and slow reaction. 2+ When the concentration exceeds a certain threshold, it will induce cell apoptosis through various mechanisms, leading to serious physiological disorders such as muscle stiffness, liver and kidney damage.
[0003] According to WHO guidelines on drinking water quality, Cu 2+ The maximum permissible limit is 2 mg / L. However, with the rapid development of industry, copper has become an important source of inorganic pollutants. For example, in the industrial field, metal processing and machinery manufacturing companies, electronic production companies and electroplating companies will produce wastewater and waste containing Cu²⁺; in agricultural production, excessive use of copper-containing pesticides will cause the concentration of copper ions in the soil to rise, which will not only affect plant growth, but may also enter the human body through the food chain. The quality of copper supplements on the market (copper gluconate, copper citrate, etc.) is uneven, which also poses a threat to human health.
[0004] Given the importance of Cu²⁺ in biological and environmental systems and its impact, the detection of Cu²⁺ is of vital importance to protect human health. Traditional detection methods include inductively coupled plasma, spectroscopy, voltammetry, mass spectrometry, etc., but traditional detection methods are usually complicated and time-consuming, with low sensitivity, low selectivity and high practical application costs. In this context, the development of portable, low-cost and highly sensitive copper ion (Cu 2+ )Detection sensors are gaining more and more attention.
[0005] In recent years, many Cu 2+Sensors have been developed one after another. However, the new Cu 2+ However, the sensors are extremely limited, and the sensitivity of the sensors still needs to be further improved. More repeatable, simple and easy-to-use Cu 2+ Detection sensors still need to be further developed. Among them, fluorescence recognition is a commonly used Cu 2+ The identification method has the advantages of low cost and fast analysis speed. Luminescent materials with fluorescent identification function have great application potential in the field of sensing, and it is expected to prepare detectors that can replace large instruments and be used for portable identification.
[0006] Coordination polymers (CPs) are metal-ligand compounds with 1D, 2D, or 3D extended structures formed by the coordination of inorganic metal ions / metal groups and ligands, usually referred to as complexes. Among the raw materials for synthesizing complexes, organic ligands are the most important component. Among the organic ligands for synthesizing complexes, most require a large amount of organic synthesis, which takes a long time, is relatively expensive, and often has certain pollution. The development of non-toxic or low-toxic organic ligands for complex synthesis is one of the urgent problems to be solved in this field. Summary of the invention
[0007] In view of the problems existing in the prior art, the present invention provides a nickel-based complex crystal material and a preparation method and application thereof.
[0008] The present invention is achieved through the following technical solutions:
[0009] A nickel-based complex crystal material, wherein the ligand of the nickel-based complex crystal material is 1,4-bis(imidazol-1-yl)benzene bib, and the structural formula is ; The auxiliary agent is L-glutamic acid, the structural formula is ; Metal salt is Ni(CH3COO)2 . 4H2O or NiCl2·6H2O;
[0010] When the metal salt is NiCl2·6H2O, the chemical formula of the nickel-based complex crystal material is [Ni(bib)2(HCOO)2] n ;
[0011] When the metal salt is Ni(CH3COO)2 . 4H2O (Ni-1), the chemical formula of the nickel-based complex crystal material is [Ni (bib) 1.5 (HCOO)2(H2O)] n (Ni-2) 。
[0012] In the present invention, the amino (-NH2) and carboxyl (-COOH) functional groups in L-glutamic acid can temporarily coordinate with metal ions to inhibit excessive crystal growth, thereby regulating the crystal growth rate and preventing the formation of irregular particles. In addition, L-glutamic acid can both release protons (acidic) and accept protons (alkaline) in water to control the pH value of the solution, thereby regulating the solubility of metal ions and the assembly environment of MOF.
[0013] Furthermore, the structure of Ni-1 belongs to the monoclinic system. P 21 / c space group, Ni-1 unit cell parameters are: a=7.4611(3) Å, b=11.6265(5) Å, c=13.6111(5) Å, α =90, β =98.410(2), γ = 90.
[0014] Furthermore, the asymmetric structural unit of Ni-1 contains one Ni 2+ , 2 bib ligands and 2 HCOO - ;Ni 2+ The coordination number of Ni is 6, which is coordinated with 4 N atoms from bib ligands and 2 O atoms from formate. 2+ The octahedral coordination structure is formed as the center, in which four N atoms form a plane and two O atoms of formate are located axially; therefore, each Ni 2+ Linking four bib ligands to form a two-dimensional layered structure, the structure is simplified to a (4,4)-grid structure with a side length of 13.61×13.81;
[0015] In Ni-1, due to the large space of each grid in the (4,4)-grid structure, which is 13.61 Å × 13.81 Å, two bib chains from other layered structures pass through each grid in the vertical direction, eventually forming an interlaced 3D structure.
[0016] Furthermore, the structure of Ni-2 belongs to the monoclinic system. C 2 / c Space group, Ni-2 unit cell parameters are: a = 2.44314 (16) Å, b = 1.22231 (9) Å, c = 1.87988 (14) Å, α = 90, β = 122.030(2), γ = 90.
[0017] Furthermore, the asymmetric structural unit of Ni-2 contains one Ni 2+ , 3 / 2 bib ligands, 2 HCOO- and 1 coordinated water molecule; Ni 2+ The coordination number is 6, which is coordinated with 3 N atoms from bib ligands, 2 O atoms O1 and O3 from formate, and 1 O atom O5 from a water molecule. 2+ It is connected to three Bib ligands to form a one-dimensional ladder-like chain structure.
[0018] In Ni-2, each Ni 2+ Connected to three bib ligands, the adjacent Ni 2+ A one-dimensional ladder-shaped chain structure is formed through bib ligand connection. The side lengths of the smallest quadrilateral structure contained in the ladder-shaped structure are 13.47 Å and 13.66 Å, respectively. The large spaces result in two other ladder-shaped chains interspersed in each quadrilateral structure, eventually forming a 3D structure.
[0019] The present invention also provides a method for preparing a nickel-based complex crystal material Ni-1, comprising the following steps:
[0020] Weigh NiCl2·6H2O (23.7 mg, 0.1 mmol), ligand 1,4-bis(imidazol-1-yl)benzene (21.0 mg, 0.1 mmol), and L-glutamic acid (14.7 mg, 0.1 mmol) in a 20 mL reactor, and add 9 mL of a mixed solution of N,N-dimethylformamide (DMF) and water (volume ratio 1: 1) to the above sample bottle. After sealing the sample bottle cap, place it in an oven and heat it at 150°C for 72 hours. When the system slowly cools to room temperature, blue transparent crystals [Ni(bib)2(HCOO)2] are obtained. n。
[0021] The present invention also provides a method for preparing a nickel-based complex crystal material Ni-2, comprising the following steps:
[0022] Weigh Ni(OAc)2 . 4H2O (24.8 mg, 0.1 mmol), ligand 1,4-bis(imidazol-1-yl)benzene (21.0 mg, 0.1 mmol), L-glutamic acid (14.7 mg, 0.1 mmol) were placed in a 20 mL reactor, and 9 mL of a mixed solution of N,N-dimethylformamide (DMF) and water (volume ratio 1: 1) was measured and placed in the above sample bottle. After the sample bottle cap was sealed, it was placed in an oven and heated at 150°C for 72 hours. When the system slowly cooled to room temperature, pink transparent crystals [Ni(bib) 1.5 (HCOO)2(H2O)] n .
[0023] The present invention also provides the nickel-based complex crystal material in Cu 2+ Identification applications.
[0024] The invention also provides application of the nickel-based complex crystal material in solvent identification.
[0025] Beneficial technical effects of the present invention:
[0026] Generally speaking, coordination polymers with good thermal stability are more suitable for identification materials and are more easily applied to high-temperature and complex environments. The thermal degradation process of coordination polymers is often accompanied by the breaking of coordination bonds and the combustion of ligands. Therefore, the thermal stability of coordination polymers is generally related to the strength of coordination bonds and the number of links of node ligands. 2+ The coordination number of the adjacent Ni in Ni-1 is 6. 2+ The bib ligands are connected to form a (4,4)-grid structure. Due to the large space of the grid, it is interlaced with two identical layered structures to form a 3D structure. This increases the stability of the complex structure. Thermogravimetric analysis shows that the main skeleton of Ni-1 remains stable before 430°C, and the entire framework begins to collapse after 430°C. Ni-2 is a 3D structure formed by chain interlacing. The main skeleton loses less weight in the range of 100~220°C, corresponding to the release of coordinated water molecules. Thereafter, it loses weight rapidly, indicating that the structure after dehydration, Ni 2+ The coordination number becomes 5, the structure becomes unstable and begins to decompose. Good thermal stability helps promote the application of Ni-1 and Ni-2.
[0027] Through multiple experiments, it was verified that the optimal excitation wavelengths of the ligand bib and the complexes Ni-1 and Ni-2 were 270 nm, 246 nm and 252 nm, respectively. When the excitation wavelength was 270 nm, the strongest emission peak of bib was located near 318 nm; when the excitation wavelength was 246 nm, Ni-1 had a small shoulder peak near 320 nm, and the strongest emission peak was located near 393 nm; when the excitation wavelength was 252 nm, the strongest emission peak of Ni-2 was located near 388 nm. When Ni-1 and Ni-2 were added to different solvents, the excitation wavelength remained unchanged (Ni-1: 246 nm; Ni-2: 252 nm), and the fluorescence emission spectra changed significantly. The positions of the strongest emission peaks of the two complexes were both near 318 nm, but the fluorescence intensities were significantly different for different solvent molecules. The fluorescence intensity of the two complexes decreased significantly after adding N-pyrrolidone (abbreviated as NMP), N,N-dimethylacetamide (abbreviated as DMA), N,N-diethylacetamide (abbreviated as DEF), and N,N-dimethylformamide (abbreviated as DMF), indicating that they have a certain recognition effect on the above four solvent molecules. The order of fluorescence intensity of Ni-1 in different solvents is: CH3OH>CH3CH2OH>CH3CN>H2O>Diox>DMSO>NMP>DMA>DEF>DMF; for Ni-2, the order of fluorescence intensity in different solvents is: CH3CH2OH>CH3OH>CH3CN>H2O>DMSO>Diox>NMP>DMF>DEF>DMA.
[0028] When Ni-1 and Ni-2 were added into 0.001 mmol / mL NaNO3, KNO3, AgNO3, Co(NO3)2, Ni(NO3)2, Cu(NO3)2, Zn(NO3)2, Cd(NO3)2, Pb(NO3)2, Fe(NO3)3, Al(NO3)3 and rare earth metal salts Y(NO3)3, La(NO3)3, Ce(NO3)3, Pr(NO3)3, Nd(NO3)3, Sm(NO3)3, Eu(NO3)3, Gd(NO3)3, Tb(NO3)3, Dy(NO3)3, Er(NO3)3, Tm(NO3)3, Yb(NO3)3 and Lu(NO3)3 solutions prepared with ethanol as solvent, the strongest emission peak position was at 318 nm compared with the blank sample without adding metal salts. nm, there is a small red shift, but the fluorescence intensity changes significantly. For Ni-1, different metal ions have different effects on the luminescence intensity of Ni-1. The order of fluorescence intensity is: Na + >Lu 3+ >Sm 3+ >La 3+ >Dy 3+ >Nd3+ >K + >Gd 3+ >Eu 3+ >Yb 3+ >Pr 3+ >Fe 3+ >Er 3+ >Tb 3+ >Tm 3+ >Pb 2+ >Y 3+ >Co 2+ >Cd 2+ >Zn 2+ >Ce 3+ >Ni 2+ >Al 3+ >Ag + >Cu 2+ . Ni is added 2+ 、Al 3+ 、Ag + , Cu 2+ After adding Cu 2+ After that, obvious fluorescence quenching occurred, and the fluorescence quenching rate was about 99.54%, which indicated that Ni-1 2+ It has high selectivity. For Ni-2, different metal ions have different effects on the luminescence intensity of Ni-2. The order of fluorescence intensity is: Na + >Pr 3+ >Gd 3+ >La 3+ >Lu 3+ >Pb 2+ >Nd 3+ >Tm 3+ >K + >Tb 3+ >Y 3+ >Fe 3+ >Er 3+ >Dy 3+ >Yb 3+ >Cd 2+ >Sm 3+ >Eu 3+ >Zn 2+ >Ce 3+ >Co 2+ >Al 3+ >Ni 2+ >Ag + >Cu 2+ . Add Cu 2+ After that, fluorescence quenching occurred, and the fluorescence quenching rate was about 99.25%, which showed that the coordination polymer Ni-2 also 2+ Therefore, when added to the Cu2+ In the solution, Ni-1 and Ni-2 can both produce fluorescence quenching. 2+ All have good recognition ability. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Schematic diagram of the coordination environment of Ni(II) in Ni-1 obtained in Example 1 (symmetric code: i 1-x, 1-y, 1-z; ii 1-x, 1-y, -z; iii 2-x, 2-y, 1-z);
[0030] Figure 2 is a diagram of the 2D layered structure present in Ni-1 obtained in Example 1;
[0031] Figure 3 The 3D intercalated structure of Ni-1 obtained in Example 1;
[0032] Figure 4 Schematic diagram of the coordination environment of Ni(II) in Ni-2 obtained in Example 2 (symmetric code: i 0.5+x, -0.5+y,z; ii 0.5-x, 1.5-y, 2-z);
[0033] Figure 5 The 1D ladder chain structure of Ni-2 obtained in Example 2;
[0034] Figure 6 The Ni-2 obtained in Example 2 is interspersed to form a 3D structure;
[0035] Figure 7 This is the infrared spectrum of the Ni-1 sample obtained in Example 1;
[0036] Figure 8 This is the infrared spectrum of the Ni-2 sample obtained in Example 2;
[0037] Fig. 9 Thermogravimetric diagram of Ni-1 obtained in Example 1;
[0038] Fig.10 Thermogravimetric diagram of Ni-2 obtained in Example 2;
[0039] Fig.11 is the solid-state fluorescence emission spectrum of the ligand 1,4-bis(imidazol-1-yl)benzene (bib);
[0040] Fig.12 is the solid-state fluorescence emission spectrum of Ni-1 obtained in Example 1;
[0041] Fig.13 is the solid-state fluorescence emission spectrum of Ni-2 obtained in Example 2;
[0042] Fig.14 The fluorescence emission spectra of Ni-1 obtained in Example 1 in different solvents;
[0043] Fig.15 The bar graph of the strongest fluorescence emission peak intensity of Ni-1 obtained in Example 1 in different solvents;
[0044] Fig.16 The fluorescence emission spectra of Ni-1 obtained in Example 1 in 11 non-rare earth metal ion solutions;
[0045] Fig.17 The bar graph of the strongest fluorescence emission peak intensity of Ni-1 obtained in Example 1 in 11 non-rare earth metal ion solutions;
[0046] Fig.18 The fluorescence emission spectra of Ni-1 obtained in Example 1 in 13 rare earth salt solutions;
[0047] Fig.19 The bar graph is a graph showing the strongest fluorescence emission peak intensity of Ni-1 obtained in Example 1 in 13 rare earth salt solutions;
[0048] Fig. 20 The fluorescence emission spectra of Ni-2 obtained in Example 2 in different solvents;
[0049] Fig.21 The bar graph of the strongest fluorescence emission peak intensity of Ni-2 obtained in Example 2 in different solvents;
[0050] Fig. 22 The fluorescence emission spectra of Ni-2 obtained in Example 2 in 11 non-rare earth metal ion solutions;
[0051] Fig.23 The bar graph of the strongest fluorescence emission peak intensity of Ni-2 obtained in Example 2 in 11 non-rare earth metal ion solutions;
[0052] Fig.24 The fluorescence emission spectra of Ni-2 obtained in Example 2 in 13 rare earth salt solutions;
[0053] Fig.25 This is a bar chart of the strongest fluorescence emission peak intensity of Ni-2 obtained in Example 2 in 13 rare earth salt solutions. DETAILED DESCRIPTION
[0054] The present invention will be further described below in conjunction with examples, but the present invention is not limited to the following examples.
[0055] Example 1
[0056] NiCl2·6H2O (23.7 mg, 0.1 mmol), the main ligand L-glutamic acid (14.7 mg, 0.1 mmol) and the auxiliary ligand 1,4-bis(imidazol-1-yl)benzene (21.0 mg, 0.1 mmol) were placed in a 20 mL reactor, and 9 mL of a mixed solution of N,N-dimethylformamide (DMF) and water (volume ratio 1: 1) was measured and placed in the above sample bottle. Finally, the sample bottle was sealed with a sample bottle cap, placed in a forced air drying oven, and heated at 150.0℃ for 3 days to obtain blue transparent crystal Ni-1.
[0057] Example 2
[0058] Ni(OAc)2 . 4H2O (24.8 mg, 0.1 mmol), the main ligand L-glutamic acid (14.7 mg, 0.1 mmol) and the auxiliary ligand 1,4-bis(imidazol-1-yl)benzene (21.0 mg, 0.1 mmol) were placed in a 20 mL reactor, and 9 mL of a mixed solution of N,N-dimethylformamide (DMF) and water (volume ratio 1: 1) was measured and placed in the above sample bottle. Finally, the sample bottle was sealed with a sample bottle cap, placed in a forced air drying oven, and heated at 150.0℃ for 3 days to obtain pink transparent crystal Ni-2.
[0059] (1) Crystal structure determination:
[0060] Crystals with better growth and fewer cracks were selected and glued to a thin glass wire. The diffraction data of Ni-1 and Ni-2 were collected under Mo-Kα radiation (λ = 0.71073 Å) at room temperature using a BrukerAPEX-II CCD single crystal diffractometer. Ni-1 and Ni-2 were refined using Shellxl-2018. The structure was solved using the XS structure solver, and the SHELXTL software package was used for least squares optimization. During the improvement process, the anisotropic displacement parameters of non-hydrogen atoms were given. The positions of hydrogen atoms on the ligands were determined using the theoretical hydrogenation method. The crystallographic data of the crystalline materials Ni-1 and Ni-2 obtained in Example 1 and Example 2 are shown in Table 1.
[0061] Table 1 Crystallographic data of Ni-1 and Ni-2 materials
[0062]
[0063] The structure of Ni-1 obtained in Example 1 is as follows Figure 1-3 As shown, Figure 1 is the coordination environment of Ni(II) in Ni-1. The asymmetric structural unit of Ni-1 contains one Ni2+ , 2 bib ligands and 2 HCOO - ;Ni 2+ The coordination number is 6, coordinated with 4 N atoms from the bib ligand and 2 O atoms from the formate group. Figure 2 is a diagram of the 2D layered structure present in Ni-1 obtained in Example 1; Figure 3 The 3D interpenetrating structure of Ni-1 obtained in Example 1 shows that in Ni-1, Ni 2+ The octahedral coordination structure is formed as the center, in which four N atoms form a plane and two O atoms of formate are located axially; therefore, each Ni 2+ Linking four bib ligands to form a two-dimensional layered structure, the structure is simplified to a (4,4)-grid structure with a side length of 13.61×13.81;
[0064] In Ni-1, since the space of each grid in the (4,4)-grid structure is large, 13.61 Å × 13.81Å, two bib chains from other layered structures pass through each grid in the vertical direction, eventually forming an interlaced 3D structure.
[0065] The structure of Ni-1 obtained in Example 2 is as follows Figure 4-6 As shown, Figure 4 Schematic diagram of the coordination environment of Ni(II). The asymmetric structural unit of Ni-2 contains one Ni 2+ , 3 / 2 bib ligands, 2 HCOO - and 1 coordinated water molecule; Ni 2+ The coordination number is 6, which is coordinated with 3 N atoms from bib ligands, 2 O atoms O1 and O3 from formate, and 1 O atom O5 from a water molecule. 2+ Connected to three bib ligands, the adjacent Ni 2+ The bib ligands form a one-dimensional ladder-shaped chain structure. The smallest quadrilateral structure contained in the ladder-shaped structure has a side length of 13.47 Å and 13.66 Å, respectively. The space is large, resulting in two other ladder chains interlaced in each quadrilateral structure, and finally interlaced to form a 3D structure. Figure 6 .
[0066] A Shimadzu FTIR-8400S spectrometer was used to analyze the −1 The FT-IR spectra of Ni-1 and Ni-2 were collected within the range of Figure 7 and Figure 8 , the results confirmed the successful coordination between metal ions and ligands.
[0067] Figure 9-10 Thermogravimetric analysis diagrams of Ni-1 and Ni-2 respectively indicate that Ni-1 and Ni-2 have good thermal stability. Ni-1 can maintain the stability of the framework structure below 430°C, and Ni-2 can maintain the stability of the framework structure below 220°C.
[0068] Figure 11-13 The fluorescence emission spectra of 1,4-bis(imidazol-1-yl)benzene bib and Ni-1 and Ni-2 at room temperature are shown in the figure. As can be seen from the figure, when the excitation wavelength is 270 nm, the strongest emission peak of the ligand is located near 318 nm; when the excitation wavelength is 246 nm, Ni-1 has a small shoulder peak near 320 nm, and the strongest emission peak is located near 393 nm; when the excitation wavelength is 252 nm, the strongest emission peak of Ni-2 is located near 388 nm. Compared with the ligand bib, the strongest emission peaks of Ni-1 and Ni-2 are red-shifted, which may be caused by the transfer of electrons between the ligand and the metal ion.
[0069] Fig.14 The fluorescence emission spectra of Ni-1 in different solvents. When the excitation wavelength is 246 nm, the strongest emission peak of Ni-1 in different solvents is around 318 nm. Compared with the solid-state fluorescence of Ni-1, the strongest emission peak shows an obvious blue shift, which may be due to the dominant role of the transfer of electrons in the ligand in the solution. The fluorescence intensity in different solvents changes significantly, and the order of fluorescence intensity is: CH3OH>CH3CH2OH>CH3CN>H2O>Diox>DMSO>NMP>DMA>DEF>DMF.
[0070] Fig.15 The bar graph shows the strongest fluorescence emission peak intensity of Ni-1 in different solvents. The fluorescence intensity of the complex Ni-1 is significantly reduced after adding NMP, DMA, DEF, and DMF, indicating that Ni-1 has a certain recognition effect on the above four solvent molecules.
[0071] Fig.16 The fluorescence emission spectra of Ni-1 in 11 non-rare earth metal ion solutions are shown in Figure 2. -3 In mmol / mL NaNO3, KNO3, AgNO3, Co(NO3)2, Ni(NO3)2, Cu(NO3)2, Zn(NO3)2, Cd(NO3)2, Pb(NO3)2, Fe(NO3)3, and Al(NO3)3 solutions, the results showed that the emission spectra had similar shapes, with the strongest emission peak near 318nm, but the fluorescence intensities were different. The order of fluorescence intensity: Na + >K + >Fe 3+ >Pb 2+>Co 2+ >Cd 2+ >Zn 2+ >Ni 2+ >Al 3+ >Ag + >Cu 2+ . Ni is added 2+ 、Al 3+ 、Ag + , Cu 2+ After adding Cu 2+ After that, obvious fluorescence quenching occurred, and the fluorescence quenching rate was about 99.54%, which indicated that Ni-1 2+ Has high selectivity.
[0072] Fig.17 The bar graph shows the strongest emission peak intensity of Ni-1 in 11 non-rare earth metal ion solutions. -3 mmol / mL NaNO3, KNO3, AgNO3, Co(NO3)2, Ni(NO3)2, Cu(NO3)2, Zn(NO3)2, Cd(NO3)2, Pb(NO3)2, Fe(NO3)3, Al(NO3)3 solutions, the strongest emission peak fluorescence intensity is different. 2+ Medium intensity is the lowest.
[0073] Fig.18 The fluorescence emission spectra of Ni-1 in 13 rare earth metal ion solutions are shown in Figure 2. -3 In mmol / mL rare earth salt La(NO3)3, Ce(NO3)3, Pr(NO3)3, Nd(NO3)3, Sm(NO3)3, Eu(NO3)3, Gd(NO3)3, Tb(NO3)3, Dy(NO3)3, Er(NO3)3, Tm(NO3)3, Yb(NO3)3, and Lu(NO3)3 solutions, the fluorescence emission spectra have similar shapes, with the strongest emission peak near 320 nm, but the fluorescence intensities are different. Compared with the blank sample, the strongest emission peaks are weakened after the addition of rare earth ions, but there is no obvious quenching phenomenon. The order of the strongest peak fluorescence intensity is: Lu 3+ >Sm 3+ >La 3+ >Dy 3+ >Nd 3+ >Gd 3+ >Eu 3+ >Yb 3+ >Pr 3+ >Er 3+ >Tb 3+ >Tm3+ >Ce 3+ .
[0074] Fig.19 The bar graph shows the strongest emission peak intensity of Ni-1 in 13 rare earth metal ion solutions. -3 The fluorescence intensity is different in mmol / mL rare earth salt La(NO3)3, Ce(NO3)3, Pr(NO3)3, Nd(NO3)3, Sm(NO3)3, Eu(NO3)3, Gd(NO3)3, Tb(NO3)3, Dy(NO3)3, Er(NO3)3, Tm(NO3)3, Yb(NO3)3, and Lu(NO3)3 solutions. 3+ The highest strength, Ce 3+ Medium intensity is the lowest.
[0075] Fig. 20 Figure 2 is the fluorescence emission spectrum of Ni-2 in different solvents. When the excitation wavelength is 254 nm, the strongest peak position of Ni-2 in different solvents is around 318 nm, but the fluorescence intensity varies greatly. The specific order of fluorescence intensity is: CH3CH2OH>CH3OH>CH3CN>H2O>DMSO>Diox>NMP>DMF>DEF>DMA.
[0076] Fig.21 The bar graph shows the strongest fluorescence emission peak intensity of Ni-2 in different solvents. The fluorescence intensity of the complex Ni-2 is significantly reduced after adding NMP, DMA, DEF, and DMF, indicating that Ni-2 has a certain recognition effect on the above four solvent molecules.
[0077] Fig. 22 The fluorescence emission spectra of Ni-2 in 11 non-rare earth metal ion solutions are shown in Figure 2. -3 mmol / mL NaNO3, KNO3, AgNO3, Co(NO3)2, Ni(NO3)2, Cu(NO3)2, Zn(NO3)2, Cd(NO3)2, Pb(NO3)2, Fe(NO3)3, Al(NO3)3 solutions, the results showed that the emission spectra had similar shapes, with the strongest emission peak between 317nm-327nm, but different fluorescence intensities. The order of fluorescence intensity is: Na + >Pb 2+ >K + >Fe 3+ >Cd 2+ >Zn 2+ >Co 2 + >Al 3+ >Ni 2+>Ag + >Cu 2+ . Add Al 3+ 、Ni 2+ 、Ag + , Cu 2+ After that, the fluorescence intensity was obviously weakened or even quenched. 3+ The fluorescence quenching rate of Ni 2+ The fluorescence quenching rate of Ag is about 95.55%. + The fluorescence quenching rate of Cu is about 98.11%. 2+ After that, obvious fluorescence quenching occurred, and the fluorescence quenching rate was about 99.25%, which indicated that Ni-2 2+ Highly selective recognition.
[0078] Fig.23 The strongest emission peak intensity bar graph of Ni-2 in 11 non-rare earth metal ion solutions. -3 mmol / mL NaNO3, KNO3, AgNO3, Co(NO3)2, Ni(NO3)2, Cu(NO3)2, Zn(NO3)2, Cd(NO3)2, Pb(NO3)2, Fe(NO3)3, Al(NO3)3 solutions, the strongest emission peak fluorescence intensity is different. 2+ Medium intensity is the lowest.
[0079] Fig.24 The fluorescence emission spectra of Ni-2 in 13 rare earth metal ion solutions are shown in Figure 2. -3 In mmol / mL rare earth salt La(NO3)3, Ce(NO3)3, Pr(NO3)3, Nd(NO3)3, Sm(NO3)3, Eu(NO3)3, Gd(NO3)3, Tb(NO3)3, Dy(NO3)3, Er(NO3)3, Tm(NO3)3, Yb(NO3)3, and Lu(NO3)3 solutions, the fluorescence emission spectra are similar in shape, with the strongest emission peak between 316 and 330 nm. Compared with the blank, a small amount of red shift occurs after the addition of rare earth metal ions. The strongest peak fluorescence intensity is significantly different. Compared with the blank sample, the strongest emission peak is weakened after the addition of rare earth ions. The order of the strongest peak fluorescence intensity is: Pr 3+ >Gd 3+ >La 3+ >Lu 3+ >Nd 3+ >Tm 3+ >Tb 3+ >Er 3+ >Dy 3+ >Yb3+ >Sm 3+ >Eu 3+ >Ce 3+ The weakest is Ce 3+ , the fluorescence quenching rate is about 81.61%.
[0080] Fig.25 The bar graph shows the strongest emission peak intensity of Ni-2 in 13 rare earth metal ion solutions. -3 The fluorescence intensity is different in mmol / mL rare earth salt La(NO3)3, Ce(NO3)3, Pr(NO3)3, Nd(NO3)3, Sm(NO3)3, Eu(NO3)3, Gd(NO3)3, Tb(NO3)3, Dy(NO3)3, Er(NO3)3, Tm(NO3)3, Yb(NO3)3, and Lu(NO3)3 solutions. 3+ The highest strength, Ce 3+ Medium intensity is the lowest.
Claims
1. A nickel-based complex crystal material, characterized in that: The ligand of the nickel-based complex crystal material is 1,4-bis(imidazol-1-yl)benzene bib, and the structural formula is ; The auxiliary agent is L-glutamic acid, with the structural formula ; The metal salt is Ni(CH3COO)2·4H2O or NiCl2·6H2O; When the metal salt is NiCl2·6H2O, the chemical formula of the nickel-based complex crystal material is [Ni(bib)2(HCOO)2] n , named Ni-1; When the metal salt is Ni(CH3COO)2·4H2O, the chemical formula of the nickel-based complex crystal material is [Ni(bib) 1.5 (HCOO)2(H2O)] n , named Ni-2; The structure of Ni-1 belongs to the monoclinic system. P 21 / c space group, Ni-1 unit cell parameters are: a=7.4611(3) Å, b=11.6265(5) Å, c=13.6111(5) Å, α =90, β =98.410(2), γ = 90; In the asymmetric structural unit of Ni-1, there is one Ni 2+ , 2 bib ligands and 2 HCOO - ;Ni 2+ The coordination number is 6, which is coordinated with 4 N atoms from bib ligands and 2 O atoms from formate. 2+ An octahedral coordination structure is formed as the center, in which four N atoms form a plane and two O atoms of formate are located in the axial direction; In Ni-1, each Ni 2+ Linking four bib ligands to form a two-dimensional layered structure, the structure is simplified to a (4,4)-grid structure with a side length of 13.61×13.81; in Ni-1, in the vertical direction, two bib chains from other layered structures pass through each grid, eventually forming an interlaced 3D structure; The structure of Ni-2 belongs to the monoclinic system. C 2 / c Space group, Ni-2 unit cell parameters are: a = 2.44314 (16) Å, b = 1.22231 (9) Å, c = 1.87988 (14) Å, α = 90, β = 122.030(2), γ = 90; In the asymmetric structural unit of Ni-2, there is one Ni 2+ , 3 / 2 bib ligands, 2 HCOO - and 1 coordinated water molecule; Ni 2+ The coordination number is 6, coordinated with 3 N atoms from bib ligands, 2 O atoms O1 and O3 from formate, and 1 O atom O5 from a water molecule; In Ni-2, each Ni 2+ Connected to three bib ligands, the adjacent Ni 2+ A one-dimensional ladder-shaped chain structure is formed through bib ligand connection. The side lengths of the smallest quadrilateral structure contained in the ladder-shaped chain structure are 13.47 Å and 13.66 Å, respectively. Each quadrilateral structure has two other ladder-shaped chains interspersed, eventually forming a 3D structure.
2. The nickel-based complex crystal material according to claim 1, characterized in that: The preparation method of Ni-1 comprises the following steps: Weigh 0.1 mmol NiCl2·6H2O, 0.1 mmol ligand 1,4-bis(imidazol-1-yl)benzene, and 0.1 mmol L-glutamic acid in a 20 mL reactor, and dissolve 9 mL of a mixed solution of N,N-dimethylformamide and water in a volume ratio of 1:
1. After sealing, place the mixture in an oven and heat it at 150°C for 72 hours. When the system slowly cools to room temperature, blue transparent crystals [Ni(bib)2(HCOO)2] are obtained. n。 3. The nickel-based complex crystal material according to claim 1, characterized in that: The preparation method of Ni-2 comprises the following steps: Weigh 0.1 mmol Ni(CH3COO)2·4H2O, 0.1 mmol ligand 1,4-bis(imidazol-1-yl)benzene, and 0.1 mmol L-glutamic acid in a 20 mL reactor, and dissolve 9 mL of a mixed solution of N,N-dimethylformamide and water in a volume ratio of 1:
1. After sealing, place the mixture in an oven and heat at 150°C for 72 hours. When the system slowly cools to room temperature, pink transparent crystals [Ni(bib) 1.5 (HCOO)2(H2O)] n .
4. A nickel-based complex crystal material as claimed in claim 1 in an environmental system Cu 2+ Identification applications.
5. An application of the nickel-based complex crystal material as claimed in claim 1 in the identification of NMP, DMA, DEF and DMF.
Citation Information
Patent Citations
Bis-imidazole organic ligand, metal organic framework material, preparation method and application
CN118184583A